2020
DOI: 10.1177/0300060520964024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on psoriasis risk and treatment efficacy: a meta-analysis

Abstract: Objective Psoriasis is an immune-mediated chronic inflammatory disease with skin and joint manifestations. Smoking is considered an unfavorable lifestyle factor for psoriasis. We aimed to explore the association between smoking, disease risk, and treatment efficacy in relation to psoriasis. Methods We searched the Cochrane Library, Embase, and PubMed databases for studies examining the relationship between smoking and psoriasis, up to 12 April 2020. We then conducted a meta-analysis using a fixed-effects model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 68 publications
(222 reference statements)
3
28
1
Order By: Relevance
“…The meta-analysis of prevalence studies confirmed the relationship between psoriasis and about 1.7 times greater frequency of smoking [ 61 ]. Moreover, smoking is a well-known disease-aggravating factor, poor treatment-outcome predictor, and cardiovascular event-risk factor [ 62 , 63 ]. Therefore, it is surprising that despite evident negative impact of smoking on psoriasis, patients still continued smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of prevalence studies confirmed the relationship between psoriasis and about 1.7 times greater frequency of smoking [ 61 ]. Moreover, smoking is a well-known disease-aggravating factor, poor treatment-outcome predictor, and cardiovascular event-risk factor [ 62 , 63 ]. Therefore, it is surprising that despite evident negative impact of smoking on psoriasis, patients still continued smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental and genetic factors both play a role in the development of immune-mediated cutaneous inflammation. Among the most significant environmental factors influencing psoriasis onset or disease severity/activity, are mental and physical stress [ 1 ], alcohol consumption [ 2 ], and smoking [ 3 ]. In addition, a growing body of evidence indicates that excessive body weight, nutritional factors, and diet may exacerbate the clinical manifestations of psoriasis or trigger the onset of the disease [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous meta-analyzes have tried to elucidate this unknown fact, but the final results have not been consistent. On the one hand, there are authors who reported that smoking influences the therapeutic response in patients and postulated that smokers were less likely to show disease improvement in the disease at 6 months after treatment with biologic agents than non-smokers [ 1 ], and, on the other hand, there have been studies suggesting that active smoking does not significantly affect the response to treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis published in 2020 suggests that the number of reports is limited and more studies are needed to confirm the effects of smoking and smoking cessation on the therapeutic response in patients with psoriasis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation